Acidovorax citrulli type III effector AopU interferes with plant immune responses and interacts with a watermelon E3 ubiquitin ligase - Yang, Linlin; Zhao, Mei; Zhang, Xiaoxiao; Jiang, Jie; Fei, Nuoya; Ji, Weiqin; Ye, Yunfeng; Guan, Wei; Yang, Yuwen; Zhao, Tingchang (Frontiers in Microbiology, 2023)
Acidovorax citrulli is a seed-borne bacterium that causes bacterial fruit blotch of watermelon and other cucurbit plants worldwide. It uses a type III secretion system to inject type III effectors (T3Es) into plant cells, which affect the host immune responses and facilitate pathogen colonization. However, the current understanding of the specific molecular mechanisms and targets of these effectors in A. citrulli is limited. In this study, we characterized a novel T3E called AopU in A. citrulli group II strain Aac5, which shares homology with XopU in Xanthomonas oryzae. The Agrobacterium-mediated gene transient expression system was used to study the effect of AopU on host immunity. The results showed that AopU localized on the cell membrane and nucleus of Nicotiana benthamiana, inhibited reactive oxygen species burst induced by flg22 and the expression of marker genes associated with pathogen-associated molecular pattern-triggered immunity, but activated salicylic acid and jasmonic acid signal pathways. Further investigations revealed that AopU interacts with E3 ubiquitin ligase ClE3R in watermelon, both in vitro and in vivo. Interestingly, the deletion of aopU did not affect the virulence of A. citrulli, suggesting that AopU may have functional redundancy with other effectors in terms of its role in virulence. Collectively, these findings provide new insights into the mechanism of plant immune responses regulated by A. citrulli T3Es.